The pianist = El pianista - Polanski, Roman; Hardwood, Ronald; Benmussa, Robert.; Sarde, Alain.; De Luze, Herve.; Rywin, Lew.; Molfenter, Henning .; Burrill, Timothy. (Leardervision, 2006)
La película narra la vida del pianista polaco Wladyslaw Szpilman (Adrien Brody).